Cerium Dioxide Nanoparticle Exposure Improves Microvascular Dysfunction and Reduces Oxidative Stress in Spontaneously Hypertensive Rats - Minarchick, Valerie C.; Stapleton, Phoebe A.; Sabolsky, Edward M.; Nurkiewicz, Timothy R. (Frontiers in Physiology, 2015)
The elevated production of reactive oxygen species (ROS) in the vascular wall is associated with cardiovascular diseases such as hypertension. This increase in oxidative stress contributes to various mechanisms of vascular dysfunction, such as decreased nitric oxide bioavailability. Therefore, anti-oxidants are being researched to decrease the high levels of ROS, which could improve the microvascular dysfunction associated with various cardiovascular diseases. From a therapeutic perspective, cerium dioxide nanoparticles (CeO2 NP) hold great anti-oxidant potential, but their in vivo activity is unclear. Due to this potential anti-oxidant action, we hypothesize that injected CeO2 NP would decrease microvascular dysfunction and oxidative stress associated with hypertension. In order to simulate a therapeutic application, spontaneously hypertensive (SH) and Wistar-Kyoto (WKY) rats were intravenously injected with either saline or CeO2 NP (100 µg suspended in saline). Twenty-four hours post-exposure mesenteric arteriolar reactivity was assessed via intravital microscopy. Endothelium-dependent and –independent function was assessed via acetylcholine and sodium nitroprusside. Microvascular oxidative stress was analyzed using fluorescent staining in isolated mesenteric arterioles. Finally, systemic inflammation was examined using a multiplex analysis and venular leukocyte flux was counted. Endothelium-dependent dilation was significantly decreased in the SH rats (29.68 ± 3.28%, maximal response) and this microvascular dysfunction was significantly improved following CeO2 NP exposure (43.76 ± 4.33%, maximal response). There was also an increase in oxidative stress in the SH rats, which was abolished following CeO2 NP treatment. These results provided evidence that CeO2 NP act as an anti-oxidant in vivo. There were also changes in the inflammatory profile in the WKY and SH rats. In WKY rats, IL-10 and TNF-α were increased following CeO2 NP treatment. Finally, leukocyte flux was increased in the SH rats (34 ± 4 vs. 17 ± 3 cells/min in the normotensive controls), but this activation was decreased following exposure (15 ± 2 vs. 34 ± 4 cells/min). These results indicated that CeO2 NP may alter the inflammatory response in both SH and WKY rats. Taken together, these results provide evidence that CeO2 NP act as an anti-oxidant in vivo and may improve microvascular reactivity in a model of hypertension.